THE INFLUENCE OF RETURN ON ASSETS AND LIQUIDITY ON STOCK PRICES OF TECHNOLOGY SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE PERIOD 2016-2020 - Iskandar Zulkarnain; Azimah Hanifah; Gatot Nazir Ahmad (PENANOMICS: International Journal of Economics, 2023)
Analysis of the Effect of Return on Assets and Liquidity on stock prices of Technology sector companies on the Indonesian Stock Exchange for the 2016-2020 period research objectives (1) To determine the effect of Return on Assets on stock prices of technology sector companies on the Indonesia Stock Exchange for the 2016-2020 period. (2) To determine the effect of liquidity on the stock prices of technology sector companies on the Indonesia Stock Exchange for the 2016-2020 period. (3) To determine the effect of Return on Assets and Liquidity on the stock prices of technology sector companies on the Indonesia Stock Exchange for the 2016-2020 period. The research method uses multiple regression with a sample size of 7 technology sector companies Research results (1) There is a positive and significant influence between Return on Assets (ROA) on the stock prices of technology sector companies on the Indonesia Stock Exchange for the period 2016 - 2020. (2) There is no influence on Liquidity, on the stock prices of technology sector companies on the Indonesia Stock Exchange for the period 2016 – 2020. (3) 3. There is an influenceReturn On Asset (ROA) and Liquidity together on Technology stock prices on the Indonesia Stock Exchange for the 2016 – 2020 period.